Precise correction of heterozygous SHOX2 mutations in hiPSCs derived from patients with atrial fibrillation via genome editing and sib selection - Sumer, Simon; Hoffmann, Sandra; Laue, Svenja; Campbell, Birgit; Rädecke, Kristin; Frajs, Viktoria; Clauss, Sebastian; Kääb, Stefan; Janssen, Johannes W. G.; Jauch, Anna; Laugwitz, Karl-Ludwig; Dorn, Tatjana; et al. (Stem cell reports, 2020)
Patient-specific human induced pluripotent stem cells (hiPSCs) offer unprecedented opportunities for the investigation of multigenic disease, personalized medicine, and stem cell therapy. For heterogeneous diseases such as atrial fibrillation (AF), however, precise correction of the associated mutation is crucial. Here, we generated and corrected hiPSC lines from two AF patients carrying different heterozygous SHOX2 mutations. We developed a strategy for the scarless correction of heterozygous mutations, based on stochastic enrichment by sib selection, followed by allele quantification via digital PCR and next-generation sequencing to detect isogenic subpopulations. This allowed enriching edited cells 8- to 20-fold. The method does not require antibiotic selection or cell sorting and can be easily combined with base-and-prime editing approaches. Our strategy helps to overcome low efficiencies of homology-dependent repair in hiPSCs and facilitates the generation of isogenic control lines that represent the gold standard for modeling complex diseases in vitro.
Gesehen am 30.11.2020